2017
DOI: 10.1080/19475705.2017.1289248
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of north Tabriz fault parameters using neural networks and 3D tropospherically corrected surface displacement field

Abstract: In this paper, parameters of north Tabriz fault are studied using 3D displacement field and artificial neural networks (ANNs). We provide the 3D surface displacement along the north Tabriz fault using an integration of tropospherically corrected InSAR, GPS and precise levelling data. To perform the InSAR analysis, we use the 17 ENVISAT radar acquisitions. The line of sight (LOS) displacement field was corrected using the ERA-Interim global meteorological reanalysis models. In order to calculate the 3D displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
(22 reference statements)
2
12
0
Order By: Relevance
“…Iran is generally a suitable target location for InSAR, given its relatively arid climate and sparse vegetation cover. InSAR time series methods have been applied to measure interseismic slip rates on a number of faults in the region, including the Ashkabad (5–12 mm/yr; Walters et al., 2013), Doruneh (2.5 ± 0.3 mm/yr; Mousavi et al., 2021), North Tabriz (6–10 mm/yr; Aghajany et al., 2017; Karimzadeh et al., 2013; Rizza et al., 2013; Su et al., 2016), Shahroud (4.75 ± 0.8 mm/yr; Mousavi et al., 2015), and the Minab‐Zendan‐Palami (10 mm/yr) and Sabzevaran‐Kahnuj‐Jiroft (7.4 mm/yr) fault systems (Peyret et al., 2009). However, InSAR has not previously been used to estimate the interseismic motion across the MRF, despite the potential of this technique to better constrain both the slip rate and locking depth of this important fault.…”
Section: Introductionmentioning
confidence: 99%
“…Iran is generally a suitable target location for InSAR, given its relatively arid climate and sparse vegetation cover. InSAR time series methods have been applied to measure interseismic slip rates on a number of faults in the region, including the Ashkabad (5–12 mm/yr; Walters et al., 2013), Doruneh (2.5 ± 0.3 mm/yr; Mousavi et al., 2021), North Tabriz (6–10 mm/yr; Aghajany et al., 2017; Karimzadeh et al., 2013; Rizza et al., 2013; Su et al., 2016), Shahroud (4.75 ± 0.8 mm/yr; Mousavi et al., 2015), and the Minab‐Zendan‐Palami (10 mm/yr) and Sabzevaran‐Kahnuj‐Jiroft (7.4 mm/yr) fault systems (Peyret et al., 2009). However, InSAR has not previously been used to estimate the interseismic motion across the MRF, despite the potential of this technique to better constrain both the slip rate and locking depth of this important fault.…”
Section: Introductionmentioning
confidence: 99%
“…where R d (287.05 J∕kg∕K) is the specific gas constant for dry air, R v (461.495 J∕kg∕K) is the specific gas constant for water vapor, Pðz 0 Þ is the surface pressure, e is the water vapor pressure, g m is the gravitational acceleration g averaged over the troposphere, and T is the temperature in K. 3,10 The LOS single path atmospheric delay, δL s LOS ðzÞ, neglecting refractive bending, varies with elevation for each acquisition date is 1,10 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 4 ; 1 1 6 ; 4 3 1 δL s LOS ðzÞ ¼…”
Section: Integration Methodsmentioning
confidence: 99%
“…The values of the refractive index, which is necessary in this method, is derived from ERA-I data. 3 More details about this method algorithm and its application in tropospheric delay computation and reconstruction of signal path in tropospheric sensing could be found in previous research. 15,16 4 Numerical Results…”
Section: D Ray Tracing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERA5 contains most parameters available in its predecessor, ERA-Interim, and ERA5 has some In this research, the ERA5 reanalysis data published by the European Centre for Medium-Range Weather Forecasts (ECMWF) were used to perform the 3D ray tracing technique. Previous studies have shown that this data is very useful in a variety of fields, including geodynamics and geodesy [22,23]. The ERA5 is a climate reanalysis dataset, covering the period from 1950 to the present.…”
Section: Study Area and Data Setmentioning
confidence: 99%